Conference Report: Summary of the Eleventh Annual University of Wisconsin Land O'Lakes Bioanalytical Conference. (October 2010) - DeMuth, James E; Hayes, Michael J; Amaravadi, Lakshmi; Arnold, Mark E; Briscoe, Chad; Clement, Robert P; Ho, Stacy; Ji, Qin C; Turk, Douglas J
This University of Wisconsin School of Pharmacy Bioanalytical Conference is arranged by the Extension Services in Pharmacy, the professional development department within the School. The purpose of this 4 day conference is to provide an educational forum to discuss issues and applications associated with the analysis of xenobiotics, metabolites, biologics and biomarkers in biological matrices. The conference is designed to include and encourage an open exchange of scientific and methodological applications for bioanalysis. To increase the interactive nature of the conference, the program was a mixture of lectures, poster sessions, round-table discussions and workshops. This paper summarizes the presentations at the Eleventh Annual Conference.